2019
DOI: 10.1590/1517-869220192502170693
|View full text |Cite
|
Sign up to set email alerts
|

Bone Tissue Behavior of Rats With Experimental Periodontitis Subjected to Physical Exercise

Abstract: Introduction: It is possible that physical activity protects the periodontium by mitigating excessive inflammatory response of the individual. There is some evidence from longitudinal studies and a prospective study demonstrating that physically active adults have experienced a decrease in the risk of periodontitis. To date no study has jointly explored the relationship of physical activity and periodontitis using inflammatory biomarkers. Objective: In this regard, the objective was to assess the bone tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Two experiments used millimeter, 35,36 while one experiment used pixel. 34 The results indicated that physical exercise reduces ABL during PD, which was contribute to prevent the development of PD.…”
Section: Alveolar Bone Lossmentioning
confidence: 86%
See 2 more Smart Citations
“…Two experiments used millimeter, 35,36 while one experiment used pixel. 34 The results indicated that physical exercise reduces ABL during PD, which was contribute to prevent the development of PD.…”
Section: Alveolar Bone Lossmentioning
confidence: 86%
“…The exercise intervention lasted for four weeks or more in all reports. In the involved experiments, one reported the outcomes only had the result of alveolar bone loss, 34 and one only had the result of the expression of TNF-α and IL-10. 33 The others reported complete results.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was surprising, considering that several studies in the literature have demonstrated the beneficial effects of physical training on the inflammatory process (12,23,26). Exercise normally triggers metabolic shifts that can affect inflammation, such as changes in nutrient signaling pathways like mTOR and SIRT1.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the inflammation resulting from periodontal disease can play an important role in systemic health, as various inflammatory markers are released into the bloodstream, potentially being a risk factor for systemic and cardiovascular diseases ( 11 ). To understand this process, interdisciplinary knowledge aiming at the comprehensive health of the individual is important ( 12 ).…”
Section: Introductionmentioning
confidence: 99%